The everyday functioning of joint health and safety committees in unionized workplaces: a labour perspective. Issue 2 (3rd July 2017) - Facey, Marcia; MacEachen, Ellen; Verma, Anil; Morales, Kathy
Abstract: Worker participation in the form of involvement in joint health and safety committees (JHSCs) has been associated with improvements in workplace safety and health. JHSC efficacy has been conceived in terms of outcomes such as compensation claims or lost time injury rates and existing research has focused on measuring their effectiveness and on identifying determinants and correlates. This administrative and system-level research focus means that little is known or understood about their everyday processes or about the experiences of JHSC members. We use qualitative data from 54 participants across three case studies of unionized workplaces in the healthcare, hospitality, and communication sectors to shed light on these micro‐social processes. Our findings suggest that social and power relationships can create inertia, even in unionized contexts, and that models of equal partnerships in workplace health should be developed to consider structural constraints.